Much Ado About Facebook? Evidence from 80 Congressional Campaigns in Chile. Issue 2 (3rd April 2022) - Luna, Juan Pablo; Pérez, Cristian; Toro, Sergio; Rosenblatt, Fernando; Poblete, Bárbara; Valenzuela, Sebastián; Cruz, Andrés; Bro, Naim; Alcatruz, Daniel; Escobar, Andrea
ABSTRACT: How do political candidates combine social media campaign tools with on-the-ground political campaigns to pursue segmented electoral strategies? We argue that online campaigns can reproduce and reinforce segmented electoral appeals. Furthermore, our study suggests that electoral segmentation remains a broader phenomenon that includes social media as but one of many instruments by which to appeal to voters. To test our argument, we analyze the case of the 2017 legislative elections in Chile. We combine an analysis of Facebook and online electoral campaign data from 80 congressional campaigns that competed in three districts with ethnographic sources (i.e., campaigns observed on the ground and in-depth interviews with candidates). The results of this novel study suggest that intensive online campaigning mirrors offline segmentation.